2021
DOI: 10.1016/j.ijid.2021.04.054
|View full text |Cite
|
Sign up to set email alerts
|

A disseminated Mycobacterium marinum infection in a renal transplant HIV-infected patient successfully treated with a bedaquiline-containing antimycobacterial treatment: A case report

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Treatment duration varied between 3.5 and 18 months. Although some adverse events such as nausea 66 and a mild QTc prolongation in one case 63 were reported, bedaquiline was well tolerated.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Treatment duration varied between 3.5 and 18 months. Although some adverse events such as nausea 66 and a mild QTc prolongation in one case 63 were reported, bedaquiline was well tolerated.…”
Section: Resultsmentioning
confidence: 90%
“…Of the eight human studies identified, four were case series 11 , 62 , 65 , 67 and four were case reports (Table 3 ). 63 , 64 , 66 , 68 Two of the studies were conducted by the same group 11 , 62 and had an overlap of four patients infected with M. intracellulare . However, the analyses done by these studies were completely different.…”
Section: Resultsmentioning
confidence: 99%
“…For both MT and NTM treatment and management are the same as in the general population [43], but therapy of these infections is complicated by pharmacological interactions with immunosuppressive regimens and the additive renal and hepatic toxicities in the long term [38,44]. There is little experience on newer agents such as clofazimine and bedaquiline, but have been safely used in a small retrospective SOT series [45,46].…”
Section: Tuberculous and Non-tuberculous Mycobacteriamentioning
confidence: 99%
“…M. abscessus remains a challenge for clinicians due to its large spectrum of virulence and resistance mechanisms [56 ▪ ]. A few case reports described the use of bedaquiline to treat cutaneous NTM disease [57,58]. The use of omadacycline [59], tedizolid [60 ▪ ] and linezolid [61] was also reported in single cases.…”
Section: Mycobacterial Skin Infectionsmentioning
confidence: 99%